The Application of [Bis(trifluoroacetoxy)iodo]benzene (PIFA) in the Synthesis of Nitrogen-Containing Heterocycles - Tellitu, Imanol; Domínguez, Esther (Synlett, 2012)
Direct oxidation of suitably functionalized amides by application of the hypervalent iodine reagent PIFA [bis(trifluoroacetoxy)iodo]benzene allows straightforward access to a variety of nitrogen-containing heterocycles. Comprehensive results from our group on the scope and limitations of such transformations will be highlighted. 1 Introduction2 PIFA-Mediated Electrophilic Aromatic Amidation3 PIFA-Mediated Olefin Amidation4 PIFA-Mediated Alkyne Amidation5 PIFA-Mediated Alkyne N–N and N–S Bond Formation6 Synthetic Applications of PIFA-Mediated Heterocyclization Reactions6.1 Synthesis of Pyrazoloquinolinones6.2 Synthesis of Pyrrolobenzodiazepine DC-81 (17)6.3 Synthesis of Pyrrolobenzodiazepines 71 and 776.4 Formal Synthesis of (±)-Clausenamide6.5 Synthesis of Polyhydroxylated Indolizidines7 Conclusions
Keywords: heterocycles; hypervalent iodine; olefin amidation; alkyne amidation; aromatic amidation